Tourism and Economic Growth (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Tourism is the process of people traveling from one place to another, mainly for recreation, sightseeing, cultural exploration, or other purposes. Tourism, as an economic activity, plays an important role in many countries and creates jobs in various sectors (transport, hotel business, catering, etc.).